Abduction! - Kehret, Peg (New York Dutton Children's Books, 2004)
Thirteen-year-old Bonnie has a feeling of foreboding on the very day that her six-year-old brother Matt and their dog Pookie are abducted, and she becomes involved in a major search effort as well as a frightening adventure. Matt is missing. Bonnie's brother left his classroom to use the bathroom --and disappeared. A police dog traces his scent to the curb, where he apparently got into a vehicle. But why would Matt go anywhere with a stranger? Overwhelmed with fear, Bonnie discovers that her dog is gone, too. Was Pookie used as a lure for Matt? Bonnie makes one big mistake in her attempt to find her brother. In a chilling climax on a Washington State ferry, Bonnie and Matt must outsmart their abductor or pay with their lives.
760L
Accelerated Reader/Renaissance Learning
A Junior Library Guild selection.
85424
Keywords: Kidnapping -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Fathers and sons -- Juvenile fiction; Seattle (Wash.) -- Fiction